FINALITY OF INDONESIAN CONSTITUTIONAL COURT DECISION IN REGARD TO JUDICIAL REVIEW - Suwarno Abadi (Fakultas Hukum Universitas Gadjah Mada, 2016)
This article examines the constitutional status of Constitutional Court’s decisions constitutionally guaranteed as final. This status very critical because it could lead Constitutional Court to the judicial supremacy position. This article argues against this possibility. The status of Constitutional Court’s decisions should be critized on the basis that its finality is prima facie, not absolute. As a solution, this article takes a position called departmentalism which means that court and legislature are not supreme in their authority to interpret the constitution. Artikel ini membahas tentang status konstitusional putusan Mahkamah Konstitusi yang dijamin konstitusi bersifat final. Status tersebut sangat kritikal karena dapat mengarahkan Mahkamah Konstitusi ke posisi supremasi yudisial. Artikel ini berargumen tidak setuju atas kemungkinan tersebut. Oleh karena itu, status putusan Mahkamah Konstitusi perlu dikritisi dengan dasar bahwa finalitasnya tersebut bersifat “prima facie”, tidak absolut. Sebagai solusinya, artikel ini mengambil posisi departementalisme yang memiliki pengertian bahwa pengadilan dan legislator tidak memiliki supremasi atas kewenangan untuk melakukan interpretasi konstitusi.